Risk factors for dengue outbreaks in Odisha, India: A case-control study. Issue 4 (April 2020) - Swain, Subhashisa; Bhatt, Minakshi; Biswal, Debasish; Pati, Sanghamitra; Soares Magalhaes, Ricardo J.
Abstract: Background: Environmental and climatic risk factors of dengue outbreak has been studied in detail. However, the socio–epidemiological association with the disease is least explored. The study aims to identify the social and ecological factors associated with emerging dengue in Odisha, India. Methods: A population-based case-control study (age and sex matched at the ratio of 1:1) was conducted in six districts of the state in 2017. A structured validated questionnaire was used to collect information for each consenting participant. An ecological household survey was done using a checklist during the month of July–September. Along with the descriptive statistics, conditional logistic regression model was used to calculate the adjusted odds ratio using STATA. Results: Of 380 cases, nearly 55% were male and the median age was 33 years. The adjusted odds of having dengue was nearly three times higher among the people having occupation which demands long travel, presence of breeding sites (1.7; 95% CI 1.2–2.6), presence of swampy area near home (1.5; 95% CI 1.1–2.1) and having travel history close to the index date (1.6; 95% CI 1.1–2.4). People staying in thatched houses had three times higher risk of the disease, however, households keeping the swampy areas clean had 50% less risk for the disease (0.5; 95% CI 0.31–0.67). Nearly 22.2% of cases had a travel history during the index date. Of them, 36% had diagnosis before the travel, whereas, 64% developed the disease after the returning from the travel. Conclusion: Household factors such as occupation and ecological condition of households play important roles in dengue outbreaks in Odisha. However, our study suggests travel/commuting are also essential factors to be considered during disease prevention planning.